Risk of falling in mild cognitive impairment: Relationships with diminishing regional cerebral metabolism and clinical parameters in a long‐term prospective longitudinal multi‐center study. (31st December 2021) - Zhang, Lorena; Liu, Stephen; Silverman, Daniel H
Abstract: Background: We recently identified visual cortex and cerebellar vermis as the cortical and non‐cortical brain areas, respectively, in which declining metabolism was most predictive of falling ( Soc. Nucl. Med. Molec. Imaging, 2021.) We now describe alterations in relationships between rates of change in their metabolism, and cognitive/functional performance. Method: Of 226 FDG‐PET brain scans from 113 Alzheimer's Disease Neuroimaging Initiative MCI subjects analyzed, 122 were from subjects (MCI‐F, n=61) suffering a fall subsequent to baseline PET, while 104 were from age‐matched subjects (MCI‐N, n=52) having no documented falls. MCI‐F scans were taken from baseline and last time point preceding date of first fall; MCI‐N scans were taken from baseline and last time point available. Magnitudes of regional metabolism in standardized volumes of interest (sVOI's) were normalized to metabolism of each subject's pons. Rates of longitudinal change were calculated as the interval difference in magnitudes between each sVOI pair divided by interval time. Significance of associations between metabolic changes and changes in overall cognition (MMSE), function (FAQ) and four individual domain scores were assessed following Bonferroni‐type statistical correction for multiple comparisons. Result: In the vermis of MCI‐N subjects, changes in metabolism correlated with changes in overall cognition and function (p=0.00007, p=0.00003, respectively); among individual cognitive domains, metabolic changes most significantly correlated with changes in visuospatial (p=0.005) and language (p=0.001) scores. Interestingly, among MCI‐F subjects, vermis metabolism declined severalfold faster than in their MCI‐N counterparts, while significant associations with changes in MMSE and FAQ (both p>0.30) as well as with visuospatial changes (p>0.99) were entirely lost, yet language changes remained strongly correlated (p=0.00004). Similarly, in bilateral visual cortex of MCI‐N, changes in metabolism correlated with changes in MMSE and memory, and those associations were lost in MCI‐F. Conclusion: Metabolism of cerebellar vermis ‐ critical for maintenance of upright posture and locomotion ‐ and of visual cortex ‐ known to diminish in patients with Lewy body involvement (associated with orthostatic hypotension and gait disturbance, both in turn increasing fall risk) ‐ not only underwent accelerated decline, but metabolic decline also became dissociated from cognitive and functional performance in MCI‐F, prior to their first documented fall.